Effective sorptive removal of five cationic dyes from aqueous solutions by using magnetic multi-walled carbon nanotubes - Guobin Song; Yawei Shi; Haonan Wang; Anqi Li; Wanran Li; Ya Sun; Guanghui Ding (Water Science and Technology, 2022)
The excellent properties of micro-nano materials and structures have attracted extensive attention especially in wastewater treatment. Based on this, magnetic multi-walled carbon nanotubes (MMWCNTs) have been prepared and used for the sorptive removal of five typical cationic dyes from aqueous solutions in the present study. Effects of several operational and environmental factors were investigated carefully, including initial pH values, common ions, contact time and temperature. The kinetics processes were well fitted by the pseudo-second-order kinetic model. The maximum adsorption capacities on MMWCNTs at 298.15 K for malachite green oxalate, auramine O, neutral red, crystal violet and rhodamine B were 442.2, 295.2, 183.4, 165.3 and 143.0 mg g−1, respectively. Differences in the size, structure and properties of these dyes led to the difference of adsorption amounts. ΔG0 were all negative within the temperature range tested, which meant the adsorption processes were spontaneous in nature. Moreover, the adsorption processes of targeted dyes, except auramine O, were exothermic and entropy decreasing. The regeneration studies indicated that the MMWCNTs showed high reusability and removal efficiencies above 75% can be achieved after four consecutive cycles. For the adsorption mechanism, electrostatic interaction, hydrogen bonds, π-π interaction together with hydrophobic interaction could coexist during the adsorption process. HIGHLIGHTS MMWCNTs were applied to the adsorption of five cationic dyes from aqueous solutions.; Various environmental factors were investigated during the adsorption process.; The MMWCNTs have high adsorption capacity for all five cationic dyes.; The MMWCNTs showed high reusability after several consecutive cycles.;